The effects of Anethum graveolens essence on scopolamine-induced memory impairment in mice - Azadeh Mesripour; Mahmoud Rafieian-Kopaei; Bahareh Bahrami (Wolters Kluwer Medknow Publications, 2016)
Since Anethum graveolens (Dill) has phytoestrogenic compounds and it is proven that estrogens exert beneficial effects on cognition; the aim of this study was to understand if this plant can improve memory performance. Male Balb/c mice weighing 25-30 g were used in this study and memory was assessed by the novel object recognition task. In this method, the difference in the exploration time between a familiar object and a novel object is taken as an index of memory performance (recognition index, RI). Scopolamine significantly reduced memory index (RI = -15.5% ± 3.0). Dill essence (100 mg/kg, ip) prevented the harmful effects of scopolamine on memory (RI = 40% ± 5.5), thus RI did not differ with control animals (RI = 50% ± 5.8). In addition, 17-β estradiol also prevented memory impairment in animals (0.2 mg/kg, ip; RI = 35.8% ± 6.5). Nevertheless, the beneficial effects of dill essence were antagonized by prior injection of tamoxifen (1 mg/kg, ip; RI = -30% ± 7.8). Although phytoesrogens are not steroids, the beneficial effect of dill on memory, at least in part, may have been achieved by estrogenic receptors present in the brain. Thus dill essence could be promising in improving memory and cognition, mainly in postmenopausal women.